Neoliberalism, globalization and symbolic violence: a web of power and resistance - GONZALES-LARA , Jorge Yeshayahu (Utopía y Praxis Latinoamericana, 2025)
This essay explores how neoliberalism, globalization, and symbolic violence shape the landscape of diasporic experiences, and how these communities deploy forms of resistance that redefine memory and identity. The study introduces the concept of Resilient Confluence of Identities, defined as the capacity of migrant communities to transform, reinterpret, and expand their cultural identities through a dynamic dialogue between their traditions of origin and the influences of the host environment. This phenomenon manifests itself in the redefinition of heritage—particularly in gastronomy, art, and literature—emerging as a strategy to counter cultural commodification and hegemonic models. Based on the theoretical frameworks of Homi K. Bhabha and Stuart Hall, the essay ultimately challenges the perception of culture as a passive element within market-driven dynamics and instead conceptualizes it as a field of struggle and social transformation. In a world where power structures are constantly being reconfigured, the resistance expressed through the Resilient Confluence of Identities demonstrates that memory and identity can act as transformative forces, challenging entrenched inequalities and redefining the meaning of progress and belonging in a globalized society.